Influence of Torsion Route on the Microstructure and Mechanical Properties of Extruded AZ31 Rods. Issue 11 (9th June 2017) - Song, Bo; Shu, Xiaogang; Pan, Hucheng; Li, Guoqiang; Guo, Ning; Liu, Tingting; Chai, Linjiang; Xin, Renlong
Abstract : Torsion deformation is an effective and simple technique to tailor the mechanical properties of Mg alloys. In this study, the influences of torsion route on microstructure and mechanical properties of AZ31 rods are investigated. The maximum torsion angle is set as 180° and the two‐pass torsion at different torsion routes, twice‐successive unidirectional torsion (TA ) and reciprocating torsion (TB ), is used to process the Mg alloy rods. It is found that the mechanical properties and yield asymmetry are very sensitive to the torsion route. Route TA is more effective for the enhancement of compressive yield strength and the improvement of yield asymmetry, while route TB is more effective for the enhancement of tensile yield strength. It is mainly attributed to the different textural evolutions between the two torsion routes. The relevant mechanisms are addressed and discussed. Abstract : Torsion deformation is an effective and simple technique to tailor the mechanical properties of Mg alloys. It is found that the mechanical properties and yield asymmetry are very sensitive to the torsion route. Route TA is more effective for the enhancement of compressive yield strength and the improvement of yield asymmetry, while route TB is more effective for the enhancement of tensile yield strength.